2017
DOI: 10.25186/cs.v12i4.1311
|View full text |Cite
|
Sign up to set email alerts
|

Morfofisiologia do crescimento vegetativo inicial de cafeeiros arabica submetidos a aplicação via foliar de Paclobutrazol

Abstract: Objetivou-se com o presente estudo avaliar respostas morfológicas e fisiológicas durante o crescimento vegetativo inicial de plantas cv. Catuaí Vermelho IAC 144 submetidas à aplicação via foliar de quatro concentrações (250, 500, 750 e 1000 mg L-1) de pacloblutrazol (PBZ) e uma testemunha. O experimento foi conduzido em casa de vegetação com uma planta por vaso, em blocos ao acaso. Avaliaram-se o diâmetro do caule, número de folhas, massas fresca e seca da planta, índice SPAD, área foliar, potencial hídrico fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…According to Brito et al (2016), Paclobutrazol causes chlorophylls concentration in a smaller volume in cells, due to product preventing cell elongation, and consequent leaf development, which was observed visually, and is also inferred at fresh mass (Figure 1). In addition, it stimulates endogenous cytokines biosynthesis, maximizing chloroplast differentiation, chlorophyll biosynthesis and delaying its degradation (D'Arêde et al, 2017). The results of the present study were close to those found by Amaral and Castilho (2012) in Bahiagrass from 39.67 to 49.60 atLEAF, when converting the values to the same unit.…”
Section: Resultssupporting
confidence: 91%
“…According to Brito et al (2016), Paclobutrazol causes chlorophylls concentration in a smaller volume in cells, due to product preventing cell elongation, and consequent leaf development, which was observed visually, and is also inferred at fresh mass (Figure 1). In addition, it stimulates endogenous cytokines biosynthesis, maximizing chloroplast differentiation, chlorophyll biosynthesis and delaying its degradation (D'Arêde et al, 2017). The results of the present study were close to those found by Amaral and Castilho (2012) in Bahiagrass from 39.67 to 49.60 atLEAF, when converting the values to the same unit.…”
Section: Resultssupporting
confidence: 91%
“…as shown in Tables (2 and 3) showed that the foliar spray of paclobutrazol on turf grass genera plants with concentrations of 750 and 1500 mg.l -1 were significantly superior to unsprayed with paclobutrazol and led to increases in most studied characters including plant density, dry root weight, color degree, coverage percentage, total chlorophyll, and carbohydrate content and the contrast led to decreased mowing number and cumulative dry weight of clipping yield these findings are consistent with those reported by Dunne et al (14) that the plant growth regulators such paclobutrazol have been demonstrated to boost leaf color and photosynthetic capability in addition to reducing clipping output, the high concentrations of paclobutrazol decrease the mowing number and cumulative dry weight for clipping yield, the main advantage of growth regulator use is a positive effect on turf grass growth and tolerance to various types of stress, thus, it is recommended for low-input maintenance turf grasses to reduce mowing expenses (27). Paclobutrazol also stimulates biosynthesis of endogenous cytokinins, maximising chloroplast differentiation, chlorophyll biosynthesis, and delaying degradation, as recorded by Arêde et al (6). Also, Volterrani et al (35) recorded that the drop in mass manufacturing has been observed to increase over time 4 weeks following pacloburazol application, mass decrease in 'Patriot' Bermuda grass (Cynodon dactylon x C. transvaalensis) was observed to be up to 91 percent.…”
Section: Discussionmentioning
confidence: 79%
“…According to Jaleel et al [12], the increase in abscisic acid contents resulting from triazole application may result in partial stomatal closure and reduction in the transpiration rate of treated plants. On the other hand, PBZ application did not alter stomatal conductance in coffee plants [45].…”
Section: Table 2 Analysis Of Variance Summary and Coefficients Of Vamentioning
confidence: 76%
“…The effect of PBZ on increasing [44] or reducing [46] the rate of CO 2 assimilation is modulated by dosage and form of application. In coffee plants, [45] found that application of lower concentrations of PBZ via leaf yielded higher photosynthetic rates and carboxylation efficiency, while higher concentrations restricted both processes.…”
Section: Table 2 Analysis Of Variance Summary and Coefficients Of Vamentioning
confidence: 97%